Pegxit Pressure: Evidence from the Classical Gold Standard - Kris James Mitchener; Gonçalo Pina (Center for Economic Studies and ifo Institute (CESifo), 2016)
We develop a simple model that highlights the costs and benefits of fixed exchange rates as they relate to trade, and show that negative export-price shocks reduce fiscal revenue and increase the likelihood of an expected currency devaluation. Using a new high-frequency data set on commodity-price movements from the classical gold standard era, we then show that the model's main prediction holds even for the canonical example of hard pegs. We identify a negative causal relationship between export-price shocks and currency-risk premia in emerging market economies, indicating that negative export-price shocks increased the probability that countries abandoned their pegs.
Keywords: F31; F33; F36; F41; N10; N20; 330; currency risk; commodity prices; exchange-rate devaluation